Intracorporeal robot‐assisted radical cystectomy, together with an enhanced recovery programme, improves postoperative outcomes by aggregating marginal gains. (3rd December 2017) - Tan, Wei Shen; Tan, Mae‐Yen; Lamb, Benjamin W.; Sridhar, Ashwin; Mohammed, Anna; Baker, Hilary; Nathan, Senthil; Briggs, Timothy; Tan, Melanie; Kelly, John D.
Abstract : Objective: To assess the cumulative effect of an enhanced recovery after surgery (ERAS) pathway and minimally invasive robot‐assisted radical cystectomy with intracorporeal urinary diversion (iRARC) in comparison with open radical cystectomy (ORC) on length of hospital stay (LOS) and peri‐operative outcomes. Materials and Methods: Between February 2009 and October 2017, 304 radical cystectomy cases were performed at a single institution (ORC, n = 54; robot‐assisted radical cystectomy [RARC], n = 250). Data were prospectively collected. We identified 45 consecutive ORC cases performed without ERAS before the commencement of the RARC programme (Cohort A), 50 consecutive iRARC cases performed without ERAS (Cohort B) and 40 iRARC cases with ERAS (Cohort C). The primary outcome measure was LOS, while secondary outcome measures included peri‐operative 90‐day complications and readmission rate. Complications were accessed using the Clavien–Dindo system. Results: Patients in all cohorts were evenly matched with regard to age, sex, body mass index, neoadjuvant treatment, tumour stage, lymph node yield, previous pelvic radiotherapy and surgery, peri‐operative anaemia, as well as physiological state. Patients who underwent iRARC with ERAS had a significantly higher American Society of Anesthesiologists score (III–IV) and were more likely to receive neobladder reconstruction. The median (interquartile range) LOS was shorter in the iRARC with ERAS group (7 [6–10]) days than in the iRARC without ERAS group (11 [8–15]) days and the ORC group (17 [14–21] days). In a propensity score‐matched cohort of patients who underwent iRARC, patients who followed the ERAS pathway had significantly lower 90‐day readmission rates. Additionally, implementing ERAS in an iRARC cohort resulted in a significantly lower 90‐day all ( P < 0.001) and gastrointestinal‐related complications ( P = 0.001). The ERAS pathway and younger patients were independently associated with an LOS of ≤10 days on multinomial logistic regression. Conclusion: A comprehensive ERAS programme can significantly reduce LOS in patients undergoing iRARC without increasing 90‐day readmission rates. An ERAS programme can augment the benefits of iRARC in improving peri‐operative outcomes. In studies comparing ORC and RARC, the presence or absence of an ERAS programme will be a confounding factor and only level 1 evidence can be interpreted reliably.